Multidrug transporter MRP4/ABCC4 as a key determinant of pancreatic cancer aggressiveness - Davio, Carlos Alberto (2021)
Pancreatic ductal adenocarcinoma (PDAC) is one of themost lethal human malignancies, due to its late diagnosis,inherent resistance to treatment and early dissemination.This type of tumor is expected to become the secondleading cause of cancer mortality by the year 2030and has limited therapeutic options. Even after the developmentof new targeted agents and the use of multipletherapeutic combinations, there is no clear benefit for thisdisease. Recent findings from our laboratory show thatMRP4 is critical for PDAC cell proliferation. Nevertheless,the significance of MRP4 protein levels and functionin PDAC progression is still unclear. Bioinformaticstudies revealed that PDAC samples show higher MRP4transcript levels compared to normal adjacent pancreatictissue and circulating tumor cells express higher levelsof MRP4 than primary tumors. Also, high levels of MRP4are typical of high-grade PDAC cell lines and associatewith an epithelial-mesenchymal phenotype. Moreover,PDAC patients with high levels of MRP4 depict dysregulationof pathways associated with migration, chemotaxisand cell adhesion. Silencing MRP4 in PANC1 cells reducedtumorigenicity and tumor growth and impaired cellmigration. Transcriptomic analysis revealed that MRP4silencing alters PANC1 gene expression, mainly dysregulatingpathways related to cell-to-cell interactions andfocal adhesion. Contrarily, overexpression of MRP4 inBxPC-3 cells produced a switch in the expression of EMTmarkers, significantly increased tumor growth, and enhancedexperimental metastatic incidence. Overall, ourfindings indicate that MRP4 upregulation could representan adaptive advantage associated with poor prognosis,evidenced by the co-expression of mesenchymal markers,higher cell proliferation, tumorigenicity and invasivenessin PDAC models. Thus, we provide theoretical andexperimental support for targeted treatment of pancreaticcancer by making an important contribution to the understandingof pancreatic tumor cell biology.